2022
DOI: 10.3390/jcm11237198
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Total Hip Arthroplasty Following Pediatric Surgical Treatment of Developmental Hip Dysplasia at 20-Year Follow-Up

Abstract: Long-term outcomes of surgical treatment for pediatric developmental dysplasia of the hip (DDH) are not well defined. The purpose of this study was to report long-term radiographic and clinical outcomes, survivorship free of total hip arthroplasty (THA), and predictors of subsequent THA following childhood treatment of DDH. This study was a single-institution retrospective review of hips treated for DDH with closed or open reduction at a minimum 10-year follow-up. 107 patients (119 hips) were included with a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Another study conducted at the Mayo Clinic, which followed patients for at least 10 years, concluded that closed reduction treatment for DDH hips did not necessitate THA. 12 However, patients who received treatment after the age of 4 years exhibited lower hip survivorship rates at the 35-year mark, with a 50% survival rate compared to 85% for those treated before 4 years of age. These findings suggest that early referral and treatment may be advantageous for the longevity of hip function.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Another study conducted at the Mayo Clinic, which followed patients for at least 10 years, concluded that closed reduction treatment for DDH hips did not necessitate THA. 12 However, patients who received treatment after the age of 4 years exhibited lower hip survivorship rates at the 35-year mark, with a 50% survival rate compared to 85% for those treated before 4 years of age. These findings suggest that early referral and treatment may be advantageous for the longevity of hip function.…”
Section: Resultsmentioning
confidence: 96%
“…Femoral osteotomy was found to be correlated with subsequent THA 11 , 12 ( Table 2 ). Table 2 also presents two studies that investigated THA outcomes for DDH patients under the ages of 20 and 30 years, respectively 13 , 14 ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The later DDH is diagnosed and treatment initiated, the worse the prognosis for the hip [ 2 ]. A possible trend towards a worse prognosis has been suggested after 18 months [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a study in 2019 found no reduction in the incidence of late-detected DDH in England over the last 35 years [ 1 ]. Another study reported that 20% of the hips treated for late-detected DDH underwent a total hip arthroplasty with 30 years of follow-up [ 2 ].…”
mentioning
confidence: 99%